2022
DOI: 10.3390/brainsci12030408
|View full text |Cite
|
Sign up to set email alerts
|

The Elephant in the Room: A Cross-Sectional Study on the Stressful Psychological Effects of the COVID-19 Pandemic in Mental Healthcare Workers

Abstract: Despite extensive research on COVID-19’s impact on healthcare workers, few studies have targeted mental health workers (MHWs) and none have investigated previous traumatic events. We investigated psychological distress in MHWs after the first lockdown in Italy to understand which COVID-19, sociodemographic, and professional variables represented greater effects, and the role of previous trauma. The survey included sociodemographic and professional questions, COVID-19 variables, and the questionnaires Life Even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 62 publications
2
25
0
Order By: Relevance
“…STS and PTSD are highly overlapping syndromes since STS in MHWs is characterized by symptoms of reliving, avoidance, and hyperarousal in response to the traumatized patients with whom they are empathically engaged [ 30 ]. According to our findings, traumatic impact when dealing with secondary exposure to stressful events is aggravated due to FCV-19 in both MHWs and HCWs [ 17 , 21 , 25 , 32 , 56 , 57 ]. However, we found that FCV-19 explained a significant yet relatively low percentage of STS variation.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…STS and PTSD are highly overlapping syndromes since STS in MHWs is characterized by symptoms of reliving, avoidance, and hyperarousal in response to the traumatized patients with whom they are empathically engaged [ 30 ]. According to our findings, traumatic impact when dealing with secondary exposure to stressful events is aggravated due to FCV-19 in both MHWs and HCWs [ 17 , 21 , 25 , 32 , 56 , 57 ]. However, we found that FCV-19 explained a significant yet relatively low percentage of STS variation.…”
Section: Discussionmentioning
confidence: 69%
“…However, the comparison of our results with those of the above studies should be considered with caution given that in many of them, FCV-19 was measured through ad hoc questions and not with validated tools. Only a few studies have examined, among other variables, the association of FCV-19 with mental health, well-being, perception of the working environment, and levels of BO in MHWs [ 17 , 21 , 22 , 24 , 25 ]. Specifically, the link between greater BO and severe FCV-19 in our study is similar with the studies by Pappa et al [ 17 ] and Rapisarda et al [ 22 , 24 ], which reported that worries about self-infection or transferring the illness were positively associated with specific aspects of BO.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations